Impacts of the Finnish service screening programme on breast cancer rates - Hakulinen Timo; Sarkeala Tytti; Anttila Ahti; Heinävaara Sirpa (BMC, 2008)
Abstract Background The aim of the current study was to examine impacts of the Finnish breast cancer (BC) screening programme on the population-based incidence and mortality rates. The programme has been historically targeted to a rather narrow age band, mainly women of ages 50-59 years. Methods The study was based on the information on breast cancer during 1971-2003 from the files of the Finnish Cancer Registry. Incidence, cause-specific mortality as well as incidence-based (refined) mortality from BC were analysed with Poisson regression. Age-specific incidence and routine cause-specific mortality were estimated for the most recent five-year period available; incidence-based mortality, respectively, for the whole steady state of the programme, 1992-2003. Results There was excess BC incidence with actual screening ages; incidence in ages 50-69 was increased 8% (95 CI 2.9-13.4). There was an increasing temporal tendency in the incidence of localised BC; and, respectively, a decrease in that of non-localised BC. The latter was most consistent in age groups where screening had been on-going several years or eventually after the last screen. The refined mortality rate from BC diagnosed in ages 50-69 was decreased with -11.1% (95% CI -19.4, -2.1). Conclusions The current study demonstrates that BC screening in Finland is effective in reducing mortality rates from breast cancers, even though the impact on the population level is smaller than expected based on the results from randomised trials among women screened in age 50 to 69. This may be explained by the rather young age group targeted in our country. Consideration whether to targeted screening up to age 69 is warranted.